2013
DOI: 10.3109/10826084.2013.841251
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Attention Deficit-Hyperactivity Disorder (ADHD) and Cannabis Use

Abstract: The current study examined the association between subtypes of attention-deficit/hyperactivity disorder (ADHD) and cannabis use within a sample of 2811 current users. Data were collected in 2012 from a national U.S. survey of cannabis users. A series of logistic regression equations and chi-squares were assessed for proportional differences between users. When asked about the ADHD symptoms they have experienced when not using cannabis, a higher proportion of daily users met symptom criteria for an ADHD diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
2
34
1
2
Order By: Relevance
“…Self-medication has been proposed as a theory to explain the association between ADHD symptoms and possible preference for various substances of abuse (69,82,84,85,186,187). The present results did not support a preference for any type of substance studied.…”
Section: Adhd and Substance Use Disordercontrasting
confidence: 90%
“…Self-medication has been proposed as a theory to explain the association between ADHD symptoms and possible preference for various substances of abuse (69,82,84,85,186,187). The present results did not support a preference for any type of substance studied.…”
Section: Adhd and Substance Use Disordercontrasting
confidence: 90%
“…The greater use of benzodiazepines and cannabis we find in our data could be attributed to the higher prevalence of psychiatric comorbidity, and to the more specific influence these substances might have on ADHD symptoms [15]. For example, the use of cannabis could be interpreted as a form of self-medication to manage sleeping problems [40] or as sedative after using stimulants [41]. It could be that neurobiological differences, impaired executive functioning, and more impulsivity contribute to increased SUD complexity in this patient group [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the effects of cannabinoids on impulsive decision making have been complex and controversial. Some studies demonstrated increased impulsive choice (Hernandez et al 2014;Loflin et al 2014) while others showed unaffected or decreased impulsive choice following cannabinoid administration (McDonald et al 2003;Pattij et al 2007;Wiskerke et al 2011). It has also been suggested that genetic factors influence the effects of cannabinoids on impulsive decision making (Boomhower et al 2013) and polymorphisms in CB1R gene is involved in differential trait impulsivity (Ehlers et al 2007).…”
Section: Discussionmentioning
confidence: 99%